Challenges of the Economic Development of Ecuador - Cerón Cerón, Hugo (2009)
To understand the country's development process, it is important to analyze both the behavior of the underdevelopment indicators, as well as the growth of the gross and demographic domestic product in Ecuador. This analysis will allow us to understand the challenges that the country faces in order to move forward on the path away from underdevelopment, which, from the point of view of this article, should focus on sectors such as ecology, politics, economy, education and the social.